Current state of the resort and tourist sphere of zaporizhzha region - Chuhunova, A. S. (ТДАТУ, 2020)
Zaporizhia region, having such a tourist and recreational potential, should enter the world tourism market, thereby attracting foreign tourists and investors. The development of the resort and tourism sector in the region will increase revenues to regional and local budgets and thus improve living standards. In addition, it will have a positive impact on the growth of demand for local industry products, increase in tourism facilities, the state of construction and infrastructure in the region, will solve the problems of employment and the environment.
Keywords: tourist potential; tourism; tourists in Zaporozhye